Pertimbangan Hukum Islam terhadap Vasektomi: Analisis Fiqh Kontemporer - Mizlan (Universitas Cokroaminoto Yogyakarta, 2025)
This study explores Islamic legal views on vasectomy through a contemporary fiqh lens, examining how rulings on male permanent contraception have evolved in response to medical, social, and ethical developments. Using qualitative descriptive methods and content analysis, it analyzes MUI fatwas and classical-contemporary fiqh texts, supported by sources on maqashid al-shariah and maslahah mursalah. The findings show a shift from strict prohibition—based on principles like hifz al-nasl—to conditional acceptance, driven by necessity and public interest. The study also highlights MUI’s evolving stance, the role of contextual ijtihad, and limited public awareness. It concludes that vasectomy can be religiously allowed under specific conditions, such as medical or economic hardship, reflecting the adaptability of Islamic law to modern reproductive health issues.